Analisis Komparasi Pengaruh Anemia dan Kekurangan Energi Kronis Selama Kehamilan terhadap Berat Badan Lahir Rendah: Meta-Analisis: Comparative Impact of Maternal Anemia and Chronic Energy Deficiency on Low Birth Weight: Meta-Analysis - Utami, Citra Tristi; Azrimaidaliza, Azrimaidaliza; Purnakarya, Idral; Dwinatrana, Khiky; Habibi, Nur Ahmad (Universitas Airlangga, 2025)
Background: Low birth weight (LBW) remains a major public health problem, particularly in low- and middle-income countries. It contributes substantially to neonatal morbidity and mortality. Some of the risk factors for LBW are maternal anemia and chronic energy deficiency (CED). These conditions are common during pregnancy and preventable. Objectives: This study aimed to analyze the comparation between maternal anemia and chronic energy deficiency during pregnancy and the risk of low birth weight. Methods: A systematic search of PubMed and Scopus was conducted for studies published between January 2020 and July 2025. Of 1,121 records identified, 22 observational studies (case–control and cohort) met the inclusion criteria. Studies evaluating the association of maternal anemia or CED with LBW were included. Data were extracted independently by two reviewers. Meanwhile, data analysis involved multiple methods. For example, pooled odds ratios (ORs) with 95% confidence intervals (CIs) were calculated using meta-analytic models. Heterogeneity was assessed using the I² statistic, and publication bias was evaluated using funnel plots. This study’s protocol was registered in PROSPERO (CRD420251138329). Discussions: From 22 studies, 19 studies assessed maternal anemia (n = 16,219), and 11 studies assessed CED (n = 4,440). Maternal CED was associated with a nearly threefold increased risk of LBW (OR = 2.98; 95% CI: 2.07–4.29; I² = 82%), while maternal anemia increased the risk by 2.4 times (OR = 2.44; 95% CI: 1.73–3.43; I² = 86%). Funnel plots showed no substantial publication bias. Conclusions: Both maternal anemia and chronic energy deficiency are significantly associated with an increased risk of low birth weight, with CED demonstrating a stronger association. Strengthening antenatal nutritional interventions is essential to prevent LBW incidences.